Age-related mitochondrial energy metabolism reprogramming occurs in granulosa cells during ovarian aging - Shi, Mengyu; Jia, Zhicheng; Yang, Xinxin; Qi, Wenlong; Sun, Xinwei; Li, Yongqian; Wang, Peixuan; Guo, Ying (Frontiers in Endocrinology, 2026)
ObjectiveOvarian aging is an inevitable age-associated biological phenomenon.Enhancing clinical pregnancy outcomes in women with advanced maternal age (AMA) has emerged as a critical research priority in reproductive medicine. The current study seeks to unravel the mechanism governing mitochondrial energy metabolism reprogramming in granulosa cells (GCs) during age-associated ovarian aging.MethodsWe conducted an age-stratified prospective observational study involving GC samples from 10 young infertile women (young group: 21–34 years) and 10 infertile women with AMA (AMA group: 35–42 years), all undergoing in vitro fertilization-embryo transfer (IVF-ET). Participants were recruited from November 2023 to November 2024. Additionally, an in vitro oxidative stress-induced senescence model was established using hydrogen peroxide (H2O2)-treated human ovarian granulosa-like tumor cell line (KGN cells) to further investigate metabolic disturbances and mitochondrial reactive oxygen species (mtROS) levels in senescent GCs.ResultsHigh-resolution targeted metabolomics revealed 25 statistically significant metabolite alterations in ovarian GCs, indicating profound dysregulation of core energy metabolism pathways—particularly oxidative phosphorylation (OXPHOS), glycolysis, and the tricarboxylic acid (TCA) cycle. Compared to the young group, the AMA group exhibited upregulated glycolytic metabolites alongside downregulated OXPHOS and TCA cycle intermediates. These findings were further validated in an H2O2-induced KGN cells senescence model, where treated cells demonstrated: (1) increased senescence-associated β-galactosidase (SA-β-gal) activity, (2) elevated extracellular acidification rate (ECAR) and lactate (Lac) production, (3) reduced oxygen consumption rate (OCR), (4) depleted glucose and pyruvate(Pyr) pools, and (5) heightened mtROS generation relative to control group.ConclusionsCollectively, our research demonstrates that GCs undergo mitochondrial energy metabolism reprogramming, characterized by a metabolic shift from OXPHOS to glycolysis, during ovarian aging. These observations suggest that age-associated glycometabolic perturbations may represent a novel therapeutic target for infertility in women with AMA.